2016
DOI: 10.1016/j.yhbeh.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Winning agonistic encounters increases testosterone and androgen receptor expression in Syrian hamsters

Abstract: Winning aggressive disputes is one of several experiences that can alter responses to future stressful events. We have previously tested dominant and subordinate male Syrian hamsters in a conditioned defeat model and found that dominant individuals show less change in behavior following social defeat stress compared to subordinates and controls, indicating a reduced conditioned defeat response. Resistance to the effects of social defeat in dominants is experience-dependent and requires the maintenance of domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 95 publications
(111 reference statements)
1
4
0
Order By: Relevance
“…Consistent with previous studies ( Zielinski and Vandenbergh 1993 ; Clinard et al 2016 ), we found higher basal serum T levels in dominant individuals ( Figure 2A ), which could partly explain their more competitive in the tube test. For CORT, our results were inconclusive, despite a trend for subordinate individuals to have higher CORT levels than dominant ones ( Figure 2B ).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies ( Zielinski and Vandenbergh 1993 ; Clinard et al 2016 ), we found higher basal serum T levels in dominant individuals ( Figure 2A ), which could partly explain their more competitive in the tube test. For CORT, our results were inconclusive, despite a trend for subordinate individuals to have higher CORT levels than dominant ones ( Figure 2B ).…”
Section: Discussionsupporting
confidence: 93%
“…While dominant hamsters show a reduced CD response compared to subordinates and animals without social status, they do not differ from SSCs in extinction of stress-induced plasma cortisol and transcription of CRH mRNA. In contrast, dominant hamsters do differ from subordinates in stress-induced neural activity within the vmPFC, medial amygdala (MeA), and lateral portions of the ventromedial hypothalamus (Morrison et al, 2014), as well as the density of androgen receptors in the MeA (Clinard, Barnes, Adler, & Cooper, 2016). The vmPFC is a key neural substrate regulating status-dependent differences in stress-related behavior because pharmacological inhibition of the vmPFC reinstates a robust CD response in dominant hamsters (Morrison et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We explore a subset of brain areas that may contribute to different aspects of territory formation and maintenance including the nucleus accumbens, hippocampus and bed nucleus of the stria terminalis. A number of other brain regions express androgen receptors and are associated with aggression are not included in this review such as the medial amygdala (Clinard et al, 2016) and ventromedial hypothalamus (Falkner et al, 2016). Most work on amygdala and hypothalamic modulation of aggression focuses primarily on intensity of aggression rather than other aspects of territoriality (Kruk et al, 1998;Yamaguchi and Lin, 2018).…”
Section: Social Vigilance a Mechanism For Deciding To Engagementioning
confidence: 99%